Design of a multi-frequency Bio-Impedance Spectroscopy system Analog Front-End and Digital Back-End with system on-chip implementation. (October 2016) - Chung, Wen-Yaw; Silverio, Angelito A.; Tsai, Vincent F.S.; Cheng, Cheanyeh; Chang, Shu-Yu; Zhou, Ming-Ying; Chen, Si-Yuan; Kao, Chi-Ying; Rustia, Dan Arcega; Lo, Yi-Wen
Abstract: In this paper, the design of an on-board and system on-chip Bio-Impedance Spectroscopy (BIS) mixed-signal system is presented. It consists of a Direct Digital Synthesis Sine-Wave Generator (DDS-SWG), an Analog Front-End (AFE), an Analog-Digital Converter (ADC), and a Digital Back-End implemented on a Field Programmable Gate Array (FPGA). The FPGA drives the ADC, the DDS-SWG, and the LCD. The AFE consists of a high output impedance Load-In-Loop Current Source (LL-CS) and High Common-Mode Rejection Ratio (CMRR) Instrumentation Amplifiers (IA). It uses a simple and straightforward impedance extraction algorithm using division and constant multiplication. Furthermore, a method that extends the AFE implementation to BIS tomography applications is presented offering low power dissipation and more chip area budget. The CMOS implementation of the AFE and the digital ASIC using TSMC 0.18 µm 1P6M are also presented. The CMOS AFE has been optimized to dissipate low power even when operating at high frequency. The system forms part of a platform that aims to predict a urolithiasis (urinary stone) event where qualitative measures of K +, Ca 2+, Cl − and Na + concentrations in urine can be obtained through impedance/ conductivity.